Asian civilization and Asian development - Wang, Linggui 1967- (Springer, 2023)
"This book focuses on the dialogues to improve the communication among Asian countries, which is contributed by world-wide experts from think-tanks, academia and governments. In this book, it involves the topics of Connotation and Evolution of Asian Civilization, Exchanges and Mutual Learning of Asian Civilization, Asian Civilization and Asian Development, Opportunities and Challenges Faced with Asian Civilization, etc. "
Keywords: Geschichte; Entwicklung; Zivilisation; Asien; Economic development / Asia; Asia / Civilization; Asia / Economic conditions; Asia / Foreign relations; Asia; Konferenzschrift -- 2019